The functional enablement relationship to performance among the administrators at the university centre-Aflou. - Moussa DHARDHARI; Ramdan AMOUMEN (Social Sciences Journal, 2021)
The study aims at finding out the relationship nature between the functional enablement and performance among a sample of administrators at the University Centre in aflou city-laghouat stat, also aiming to recognize the differences signification in the functional enablement and performance according to the variation of the scientific qualification, experience of work and their interaction To realize the study purposes, the analytical descriptive method/approach is used , where all the sample individuals of the study are limited in 93 administrators by applying the questionnaire within the essential study procedures.The study results are:The is a correlation between both of the functional enablement and performance as well as , there are statistical differences in the functional enablement related to the scientific qualification and experience of work, but there are no statistical differences in performance linked to the scientific qualification, performance and the interaction between both of them.